2008
DOI: 10.1021/np078012m
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Triterpene Saponins from the Roots of Phytolacca americana

Abstract: Five new triterpene saponins named phytolaccasaponins N-1 (1), N-2 (2), N-3 (3) N-4 (4), and N-5 (5) were isolated from the roots of Phytolacca americana together with seven known triterpene saponins (6-12). The structures of the five new saponins were established as shown in structures 1-5 on the basis of their spectroscopic data. The MDR-reversal activity of 1-12 was evaluated on the basis of the amount of calcein accumulated in MDR human ovarian cancer 2780 AD cells in the presence of each compound. The mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 26 publications
1
30
0
1
Order By: Relevance
“…Among these compounds, odoroside A (Figure 7a) was found to inhibit ICAM-1 expression induced by TNF-a or IL-1 at IC 50 values o1 mM. [119][120][121][122][123] Odoroside A has been shown to directly inhibit the ATP-hydrolyzing activity of Na + /K + -ATPase as potently as ouabain. 124 However, in contrast to previous studies, we have found that odoroside A and ouabain affect neither TNF-a-induced early NF-kB signaling pathway nor mRNA expression, but rather prevent NF-kB-inducible protein expression by blocking Na + -dependent amino acid transport.…”
Section: Cardenolide Glycosidesmentioning
confidence: 99%
“…Among these compounds, odoroside A (Figure 7a) was found to inhibit ICAM-1 expression induced by TNF-a or IL-1 at IC 50 values o1 mM. [119][120][121][122][123] Odoroside A has been shown to directly inhibit the ATP-hydrolyzing activity of Na + /K + -ATPase as potently as ouabain. 124 However, in contrast to previous studies, we have found that odoroside A and ouabain affect neither TNF-a-induced early NF-kB signaling pathway nor mRNA expression, but rather prevent NF-kB-inducible protein expression by blocking Na + -dependent amino acid transport.…”
Section: Cardenolide Glycosidesmentioning
confidence: 99%
“…EsA, which can inhibit cell growth and ICAM-1 induction, accumulate calcein in cells (Wang et al, 2008) and treat nephritis (Ju et al, 1999), did not show obvious proinflammatory or irritating effects herein. Since the content of EsA remained constant while that of EsC reduced appreciably after vinegar processing, the toxicity of P. americana may be associated more with EsC than with EsA.…”
Section: Discussionmentioning
confidence: 71%
“…Although the plant is toxic, it is used as a traditional herbal medicine in China [17,18]. The following compounds have been identified in the leaves of P. americana:…”
Section: Introductionmentioning
confidence: 99%
“…The glucosides of triterpene saponins (e.g., esculentoside B, phytolaccoside E, and esculentoside G) were extracted from the root of P. americana, and their structures were established on the basis of spectroscopic analysis [18]. Since these triterpene saponin glucosides were also obtained from cell cultures of P.…”
Section: Introductionmentioning
confidence: 99%